Hungarian Monitoring, 28 August 1988 . [Magyar rádiófigyelő], 1988. augusztus 28 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Polish United Workers' Party in session - National minorities questions in the Soviet press - Czechoslovak-West German relations Domestic Affairs: - Romanian-Hungarian summit meeting - Commemorating Balatonszárszó conference 45 years ago - Interview with Bishop of Pécs József Cserháti - Renaming Moscow Square - István Bethlen's memoirs published - The life and unexplained death of former justice minister István Reis Külpolitika: - LEMP ülés - A nemzetiségi kérdés a szovjet sajtóban - Csehszlovák-nyugatnémet kapcsolatok Belpolitika: - Román-magyar csúcstalálkozó - Megemlékezés a 45 évvel ezelőtti szárszói tanácskozásról - Interjú Cserháti József pécsi püspökkel - A mostani Moszkva tér névváltozásai - Megjelennek Bethlen István emlékiratai - Reis István egykori igazságügy miniszter élete és tisztázatlan halála